Capacitive lithium capture system using a mixed LiMn2O4and LiAlO2 material - Tasneem Elmakki (16515435) (2024)
The increasing demand for lithium (Li), a crucial material in various industries, requires efficient recovery methods and a shift toward a circular economy. This study investigates a fast, eco-friendly technique for selective Li recovery, emphasizing the use of innovative materials from spent Li-ion batteries (SLiBs), particularly LiMn2O4(LMO)/LiAlO2(LAO)-based materials, to enhance Li's circular economy. Conventional Li recovery methods typically involve prolonged processes with chemical additives and environmental concerns, whereas electrochemical systems like membrane-based capacitive deionization (MCDI) offer promising high removal capacities, regeneration ability, and scalability. However, no commercial electrochemical Li recovery system underscores the need for continued research to improve their performance. This study employs MCDI for selective Li recovery, examining various electrode materials, including commercial activated carbon, LMO-based electrodes, and modified LMO/LAO-based electrodes. The mixed LiMn2O4/LiAlO2 cathode exhibited high selectivity for Li+ extraction with a recovery efficiency of 83.1 %, achieving a deionization capacity of 38.15 mg/g at 1.0 V under an initial feed concentration of 5 mM LiCl. The Li+ adsorption reached 900 μmol/g, with a separation factor (α Mg2+ Li+ ) of 3.77 (CMg2+/CLi+ = 1), setting a robust foundation for a comprehensive Li recovery framework that meets the increasing Li demand while minimizing environmental impact. Other Information Published in: Desalination License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.desal.2024.118195